Perancangan Sistem Aplikasi Manajemen Gudang pada Industri Fabrikasi Menggunakan Metode Mobile Application Development Life Cycle - Kuncoro, Muhammad Ari (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The advancement of information technology has significantly impacted operational efficiency across various sectors, including the fabrication industry. However, many companies still face challenges in managing inventory accurately, in real-time, and in a structured manner. PT Armindo Jaya Mandiri is a company engaged in engineering and fabrication, yet it still relies on manual Excel-based records for managing raw materials, inventory, and tool assets. This has led to data discrepancies, loss of equipment, and errors in project material distribution. This research aims to design a mobile-based warehouse management system to address these issues using the Mobile Application Development Life Cycle (MADLC) approach. The system development focuses on features such as recording incoming and outgoing goods, managing material and consumable stock, handling shipping and receiving of items, as well as implementing a production tool rental system (tools asset rental). The research method used is a qualitative approach through direct observation, interviews with warehouse staff and supervisors, and literature studies. The results of this study show that the designed application system can improve warehouse operational efficiency, accelerate real-time data access, and enhance the accuracy of recording and asset tracking. Therefore, this application is expected to support production processes more effectively and be better integrated within the fabrication industry environment